Sales information system at kemplang syifa kayuagung store web-based - Apriansyah; Kemas Muhammad Wahyu Hidayat; Agung Wijaya (Yayasan Pendidikan Rafisqy Arfadhia, 2023)
This study describes the theory behind the creation of a web-based sales information system at the Kemplang Sifa Kayuagung Store using PHP and MySql. In this research, technical-qualitative method is used. The research explains the formulation of the system development problem, and a decision support system is built to solve the problem. This software development support system uses a prototyping approach and design using UML: use diagrams, activity diagrams, sequence diagrams, and class diagrams. After the design phase, the program data is implemented using the PHP programming language and MySQL database, and the testing phase begins with black box testing. In this study, the authors obtained data through interviews, observation and documentation. This test is carried out so that the system created by the author can work according to the expected specifications.